Effect of parent concrete strength on recycled concrete performance - Bachir Kebaili; Mohammed Benzerara; Souad Menadi; Nadia Kouider; Redjem Belouettar (Fracture and Structural Integrity)
Reusing concrete wastes as a secondary aggregate might be an efficient solution for long-term environmental protection and sustainable development. However, the different properties of waste concrete, particularly compressive strengths might have a negative impact on recycled concrete. The main purpose of this experimental investigation is to evaluate the influence of parent concrete quality on recycled concrete performance. Three categories of compressive strength (10 to 15 MPa), (20 to 25) MPa, and (30 to 40 MPa) are used to complete this assignment. As a random parameter, an unknown compressive strength was also incorporated. The experimental mix contains 40% secondary aggregates (both coarse and fine) and 60% natural aggregates. To achieve the necessary workability, the significant water absorption properties of recycled concrete aggregate necessitate water content adjustment. As a result, the compressive strength of recycled concrete decreases by 14 to 23.7 percent when compared to conventional concrete. To compensate for this loss, a quantity of cement content deemed to be absorbed by porous attached mortar equal to 4% of the weight of the recycled aggregate was added. The results show that the strength qualities of the original concrete have only a little impact on the compressive strength of the recycled concrete. When crushed, low compressive strength parent concrete produces a considerable volume of fine aggregate and a high proportion of clean recycled coarse aggregates with less attached mortar and has the same compressive strength as excellent parent concrete. In comparison, cement content adjustment does not enhance flexural strength; This appears to be due to a weak interface zone between the aggregate and the old adhering mortar